Staphylococcus aureus Penghasil Pigmen Kuning yang Diisolasi dari Kejadian Bumblefoot pada Broiler Lebih Patogen Dibanding Penghasil Pigmen Putih (STAPHYLOCOCCUS AUREUS PRODUCING YELLOW PIGMENT ISOLATED FROM BUMBLEFOOT CASE IN BROILER CHICKENS IS MORE PAT - ., Khusnan; Prihtiyantoro, Wahyu; Slipranata, Mitra (Jurnal Veteriner, 2015)
A study to evaluate the correlation between the pigments produced by Staphylococcus aureusisolateswith their adhesion capability on epithelial cells and phagocytes activity of macrophages in vitro.Ten S.aureus isolatesfrom bumble foot and arthritis casesin broiler were used in this study. The adhesion assaywas performed using epithelial cell derived from human buccal epithelial cells whereas phagocytic activitywas conducted using mouse peritoneal macrophage cells.The results showed that S. aureus isolates frombroiler produced both yellow and white pigments. Staphylococcus aureus producing white pigment adheredto human buccal epithelial cells with the density of about 24,25 bacteria/cell, which were higher than thoseof Staphylococcus aureus producing yellow pigmentabout 23,78 bacteria/cell. Staphylococcus aureusproducing white pigment was more phagocytosed by macrophages than S. aureusproducing yellow pigment,with an average phagocytic activiry of19,86 bacteria/cellas compared to15,96of bacteria/cell, respectively.
Keywords: S. aureus, broiler, pigment, adhesion, phagocyte